Efektivitas Metode Ekstraksi Puntung Rokok Sebagai Bioinsektisida Terhadap Mortalitas Kecoa Amerika (Periplaneta americana): Effectiveness of Cigarette Butts Extraction Method a s Bioinsecticide on Mortality of American Cockroach (Periplaneta americana) - Yusup, Dzakwan Hamzah Dhobit; Muhammad Al-Irsyad; Vivi Novianti (Aspirator, 2024)
American cockroach (Periplaneta americana) is one of the vectors of disease because there are bacteria and parasites in its body. One way to control them is by using synthetic insecticides. However, synthetic insecticides have active ingredients that are harmful to humans. Bioinsecticides can be used as an alternative, one of which is from cigarette butt waste which has active substances. Cigarette butts are a relatively large waste in Indonesia with 200,000 butts per year. This study aims to find the effectiveness of cigarette butts extract by maceration and drying methods and compare the two methods. This research is experimental using a non-factorial completely randomized design. The research was conducted with 2 methods, maceration and drying with dose of 100, 150, and 200 g/Lwith positive (synthetic insecticide) and negative controls. The treatment was repeated 4 times with a total of 32 experimental units. Each container measuring 26 x 26 x 10 cm3 contained 10 cockroaches totaling 320. Data were analyzed using One Way Anova and Kruskal Wallis with Games Howell and Mann Whitney U tests with a significant level of 5%. The highest average results from each method, maceration and drying, have the same results at a dose of 200 g/L with a mortality percentage of 70% and 55%, respectively. In the comparison of the two methods, the maceration method with a dose of 200 g/L is the most effective dose. These results indicate that cigarette butt waste can be used as an alternative bioinsecticide in controlling American cockroaches (Periplaneta Americana)